1995
DOI: 10.3171/jns.1995.83.4.0682
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth/permeability factor expression in human glioma specimens: correlation with vasogenic brain edema and tumor-associated cysts

Abstract: Peritumoral vasogenic brain edema (PVBE) is a common accompaniment of malignant gliomas. It results from microvascular extravasation of plasma fluid and proteins through the interendothelial spaces. Tumor-associated cysts (TACs) are observed more commonly with benign gliomas that are not associated with PVBE. This study investigates the hypothesis that these morphologically distinct epiphenomena of microvascular extravasation are linked by a common pathophysiological mechanism involving vascular endothelial gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
77
1
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(86 citation statements)
references
References 40 publications
4
77
1
4
Order By: Relevance
“…The epithelial expression of VEGF in RCs and RRCs might constitute an additional mechanism for the enlargement of these lesions, maintaining the stimulus for angiogenesis and vascular permeability, a role also proposed by Leonardi et al 18 Results from studies of the expression of VEGF in brain tumor cysts 13,15,17 and cyst fluid of thyroid nodules 14,16 also corroborate this suggestion. According to Vaquero et al, 15 VEGF might enhance accumulation of cyst fluid, together with an increase in oxygen supply boosting the development of the cyst.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The epithelial expression of VEGF in RCs and RRCs might constitute an additional mechanism for the enlargement of these lesions, maintaining the stimulus for angiogenesis and vascular permeability, a role also proposed by Leonardi et al 18 Results from studies of the expression of VEGF in brain tumor cysts 13,15,17 and cyst fluid of thyroid nodules 14,16 also corroborate this suggestion. According to Vaquero et al, 15 VEGF might enhance accumulation of cyst fluid, together with an increase in oxygen supply boosting the development of the cyst.…”
Section: Discussionsupporting
confidence: 77%
“…6,18 Therefore, VEGF has been implicated as an important factor in granulation tissue development 7,8,11,12 and cyst enlargement. [13][14][15][16][17] In the present study, we evaluated the expression of VEGF in PGs, RCs, and RRCs. The results revealed that VEGF is expressed in the connective tissue of all of these lesions and in the epithelial lining of RCs and RRCs, corroborating earlier studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant gliomas are still associated with poor prognosis, the mean survival time of patients with glioblastoma multiforme (GBM) is 1 year, and it has not changed significantly for the last three decades (Lopez-Gonzalez and Sotelo, 2000). Glioblastoma multiforme is accompanied by extensive angiogenesis which is essential for tumoral growth and invasiveness; it also produces a vast amount of growth factors such as PDGF, VEGF, HGF and FGF (Strugar et al, 1995;Arrieta et al, 1998Arrieta et al, , 2002Moriyama et al, 1999;Schmidt et al, 1999). In brain parenchyma there is a local RAAS, some neurons, glial cells and glioma cells express renin, angiotensinogen and receptors for Ang II (AT 1 and AT 2 ) (Ganong, 1984, Ariza et al, 1988Fogarty et al, 2002;Juillerat-Jeanneret et al, 2004).…”
mentioning
confidence: 99%
“…Despite multidisciplinary therapeutic approaches, the median survival for patients with GM is approximately 12 months after diagnosis (Lopez-Gonzalez and Sotelo, 2000;Sotelo et al, 2006). High-grade astrocytomas (AA and GM) display high cellular proliferation and extensive angiogenesis (Tuettenberg et al, 2006) stimulated by the production of growth factors such as platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), and hepatocyte growth factor (Strugar et al, 1995;Moriyama et al, 1999;Schmidt et al, 1999;Arrieta et al, 2002). Angiotensin II (ANGII) is the main effector in the renin-angiotensin-aldosterone system (RAAS) -a powerful vasoconstrictor system - (Matsusaka and Ichikawa, 1997) and acts on two membrane-bound receptors (AT1 and AT2).…”
mentioning
confidence: 99%